2021
DOI: 10.1088/2053-1591/abe977
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and intergranular corrosion properties of Inconel 625 superalloys fabricated using wire arc additive manufacturing

Abstract: Inconel 625 superalloy samples were fabricated using wire arc additive manufacturing (WAAM). The phase composition, microstructure, anti-corrosion, and mechanical properties of the Inconel 625 WAAM samples were analyzed. The microstructure of the Inconel 625 WAAM alloy showed good forming quality, no defects, and good metallurgical bonding within the specimens. The metallographic structure exhibited primarily γ-Ni and granular precipitated phases; the average microhardness of the transverse and longitudinal cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 49 publications
0
1
2
Order By: Relevance
“…In addition, some authors mentioned that the threshold for sensitization in the industry is 1 mm/year 13 , thus an acceptable friction-stir-welded alloy 625 was obtained. It is worth noting that authors 32 showed that Inconel 625, produced by wire-arc additive manufacturing (WAAM), reached an average corrosion rate of 0.609 mm/year (slightly higher than that of the current work), which was then suggested to have an excellent resistance to intergranular corrosion. Furthermore, for Inconel 686, a nickel-based alloy that was processed by fusion welding processes such as gas metal-arc welding (GMAW) and gas tungsten-arc welding (GTAW), the corrosion rate was respectively 2.5 mm/year and 2.3 mm/year 33 .…”
Section: Resultscontrasting
confidence: 51%
“…In addition, some authors mentioned that the threshold for sensitization in the industry is 1 mm/year 13 , thus an acceptable friction-stir-welded alloy 625 was obtained. It is worth noting that authors 32 showed that Inconel 625, produced by wire-arc additive manufacturing (WAAM), reached an average corrosion rate of 0.609 mm/year (slightly higher than that of the current work), which was then suggested to have an excellent resistance to intergranular corrosion. Furthermore, for Inconel 686, a nickel-based alloy that was processed by fusion welding processes such as gas metal-arc welding (GMAW) and gas tungsten-arc welding (GTAW), the corrosion rate was respectively 2.5 mm/year and 2.3 mm/year 33 .…”
Section: Resultscontrasting
confidence: 51%
“…In addition, some authors mentioned that the threshold for sensitization in the industry is 1 mm/y [13], thus an acceptable friction-stir-welded alloy 625 was obtained. It is worth noting that authors [26] showed that Inconel 625, produced by wire-arc additive manufacturing (WAAM), reached an average corrosion rate of 0.609 mm/year (slightly higher than that of the current work), which was suggested to have an excellent resistance to intergranular corrosion. Furthermore, for Inconel 686, another nickel-based alloy that was reported to be processed by gas metal-arc welding (GMAW) and by gas tungsten-arc welding (GTAW), the corrosion rate was respectively 2.5 mm/y and 2.3 mm/y [27].…”
Section: Friction-stir-welded Alloy 625contrasting
confidence: 57%
“…AM is classified into several categories based on the process being used for deposition, as shown in Figure 1; it includes powder bed fusion (PBF), direct energy deposition (DED), photopolymerization, material jetting, binder jetting, material extrusion and sheet lamination. Metal AM is mainly categorized into two groups, namely, DED and PBF (Guo et al , 2021).…”
Section: Introductionmentioning
confidence: 99%